The influence of ABCB1 and P2Y12 genetic variants on clinical outcomes in Chinese intracranial artery stenosis patients. (15th August 2018) - Li, Xingang; Jiang, Liqun; Sun, Shusen; Li, Wei; Li, Xiaoqing; Miao, Zhongrong; Zhao, Zhigang; Ma, Ning
Summary: For intracranial artery stenosis patients, high inter‐individual variability in response to antiplatelet drug therapy results in recurrent ischaemic events. We aimed to evaluate the association of drug‐related genetic polymorphisms with adverse clinical outcomes. We consecutively enrolled 157 patients receiving dual‐antiplatelet therapy (aspirin plus clopidogrel), and adverse clinical events occurred in 10 patients during the 1 year follow‐up. The P2Y12 polymorphisms (rs9859538 and rs10935842) were associated with increased likelihood of relapse events (OR = 2.934, 95% CI = 1.022‐8.425, P ‐value = .045), and the 2 variants are in complete linkage disequilibrium. The mutation of ABCB1 rs1128503 may decrease the recurrence of clinical events (OR = 0.211, 95% CI = 0.046‐0.957, P ‐value = .044). Genetic testing (ABCB1 and P2Y12) may provide useful information to prevent ischaemic events prior to the initiation of antiplatelet therapy.